Impact of the Balloon Inflation Time and Pattern on the Coronary Stent Expansion - Jarosław Skowroński; Rafał Wolny; Jan Jastrzębski; Paweł Tyczyński; Karol Szlazak; Jerzy Pręgowski; Gary S. Mintz; Karolina Liżewska; Wojciech Świeszkowski; Zbigniew Chmielak; Adam Witkowski (Journal of Interventional Cardiology)
Objectives. To assess the expansion pattern of coronary stents by using different balloon inflation times and pressures. Background. The selection of coronary stent size and its proper deployment is crucial in coronary artery interventions, having an impact on the success of the procedure and further therapy. Methods. Ten pairs of different stents were deployed under nominal pressure using sequential (5, 5, 10, and 10 seconds of repeated inflations, thus 30 seconds of summarized time) and continuous (30 seconds) deployment pattern. After each given time-point, intraluminal stent measurements were performed by optical coherence tomography (OCT) and intravascular ultrasound (IVUS). Results. Both in-stent diameters and cross-section areas (CSA) of paired stents measured by OCT at all sequential time-points were significantly smaller compared to given manufacturers charts’ values (90% to 94% for diameters and 81% to 88% for CSA, p<0.05). Significant increase of in-stent diameter and CSA was observed across the step-by-step deployment pattern. In-stent lumen measurements were significantly larger when sequential deployment pattern was applied compared to continuous deployment. Additional measurements were also done for overlapping segments of stents, showing smaller in-stent measurements of the latter compared to nonoverlapping segments. Validation of OCT and IVUS measurements using a phantom metallic tube showed perfect reproducibility with OCT and overestimation with IVUS (8% for diameters and 16% for CSA). Conclusions. Stent diameter after deployment is time-dependent and not only pressure-dependent. Different stent expansion behavior, depending on the applied deployment pattern (sequential and nonsequential), was observed.